Pollinator dependency, pollen limitation and pollinator visitation rates to six vegetable crops in southern India - Davidar, Priya; Carr, Saranya Arwen (Journal of Pollination Ecology, 2015)
We investigated levels of pollinator dependency and pollinator visitation rates to flowers of six vegetable crops: brinjal (aubergine), tomato, chilli pepper (Solanaceae), okra (Malvaceae), bitter and snake gourds (Cucurbitaceae) in six small family farms in the Coimbatore region of southern India. We tested the null hypothesis that fruit set in these crops would be independent of pollinators. We assessed fruit set through self and cross pollination by pollen augmentation, by pollinator exclusion and open pollination. We evaluated pollen limitation by comparing percentage fruit set by hand outcrossed pollen with open pollination; pollinator dependency by differences in percentage fruit set by open pollination and autogamous pollination; and visitation rates to flowers by pollinating insects. Tomato, chilli and okra produced self-compatible hermaphrodite flowers, with higher levels of autogamous fruit set (32-76%) and significantly lower levels of pollinator dependency (0-37%), whereas andro-monoecious brinjal and monoecious gourds had significantly lower levels of fruit set through autogamy, and higher levels of pollinator dependency. Pollen limitation was not evident in any crop. Diverse pollinating insects visited the flowers, and the frequency of visits by different pollinator taxa differed with crop type. Native vegetation and uncultivated land may enhance pollinator diversity in small farms.